Development and Validation of a Sensitive LC–MS-MS Method for Quantification of Mogrol in Rat Plasma and Application to Pharmacokinetic Study. (24th November 2016) - Luo, Zuliang; Zhang, Kailun; Shi, Hongwu; Guo, Yuhua; Ma, Xiaojun; Qiu, Feng
Abstract: Mogrol, the aglycone of mogrosides, is a potential pharmacologically active ingredient isolated from the fruits of Siraitia grosvenorii . The aim of this study was to develop and validate an LC–MS-MS method for the quantification of mogrol in rat plasma. Protein precipitation extraction procedure using methanol/water (1:1, v/v) was employed to extract mogrol from rat plasma. Chromatographic separation was performed on a reverse-phase Agilent Zorbax XDB C18 column (50 mm × 2.1 mm, 3.5 μm) with gradient elution using a mobile phase containing methanol and water, both of which contained 0.1% formic acid at a flow rate of 0.50 mL/min. The analyte was monitored by tandem-mass spectrometry with positive electrospray ionization mode. The precursor/product transitions ( m/z ) in the positive ion mode were 459.3→423.3 and 386.2→122.3 for mogrol and internal standard, respectively. The method was validated over the concentration range of 10.0–10, 000 ng/mL with a lower limit of quantification of 10.0 ng/mL in rat plasma. Validation experiments included tests for specificity, precision, accuracy, matrix effect, and stability under different storage and handling conditions. This method was successfully utilized to pharmacokinetic evaluation of mogrol after intravenous and oral administration of a single dose in rats at 2.0 and 5.0 mg/kg, respectively. The oral absolute bioavailability ( F ) of mogrol was estimated to be 10.3 ± 2.15% with an elimination half-life ( t 1/2 ) value of 2.41 ± 0.11 h.